2021
DOI: 10.3389/fresc.2021.724589
|View full text |Cite
|
Sign up to set email alerts
|

Canadian Resources for Siblings of Youth With Chronic Health Conditions to Inform and Support With Healthcare Management: A Qualitative Document Analysis

Abstract: Background: As children and adolescents with a chronic health condition (CHC) age and transition to adulthood, many will increasingly assume responsibilities for the management of their healthcare. For individuals with CHCs, family members including siblings often provide significant and varied supports. There are a range of resources in Canada to support siblings of individuals with a CHC, but these resources are not synthesized and the extent to which they relate to healthcare management remains unclear.Purp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…Despite the need for discussions about future planning with the whole family, a previous review of the grey literature about resources for siblings to support with healthcare management identified no resources to facilitate family conversations for future planning . Members of the SibYAC described the valuable role that they have to their sibling with a disability, and there should be conversations with parents, service providers and professionals about these roles (Bellefeuille et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the need for discussions about future planning with the whole family, a previous review of the grey literature about resources for siblings to support with healthcare management identified no resources to facilitate family conversations for future planning . Members of the SibYAC described the valuable role that they have to their sibling with a disability, and there should be conversations with parents, service providers and professionals about these roles (Bellefeuille et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…A review and analysis of online resources found that siblings shared in blogs and interviews about the roles and responsibilities that they have to their sibling with a neurodisability, such as providing support and attending therapy appointments (Nguyen et al, 2021). Siblings also shared information about the emotions they experience when they assume many of these roles, including feelings of frustration, guilt and stress, as well as love and care for their sibling with a neurodisability (Nguyen et al, 2021). While siblings have shared brief descriptions of their roles, details are needed about the types of roles that siblings have to their sibling with a neurodisability during the transition to adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…In our review of online resources [ 149 ], siblings identified in blogs and interviews about the importance of first acquire knowledge about the NDD of their sibling before they could learn specific skills. In addition to knowledge, the siblings also learned about coping skills to address the challenges that they experienced in their sibling relationship.…”
Section: Discussionmentioning
confidence: 99%
“…The siblings participating in programs may wish to access additional resources for their learning. For example, a review of sibling resources was recently synthesized across children’s hospitals, organizations, and treatment centers in Canada that could be shared with siblings [ 149 ]. Existing programs could consider how to expand the content of their programs with resources that the siblings may refer to.…”
Section: Discussionmentioning
confidence: 99%
“… 32 This is particularly relevant when examining the roles and responsibilities of siblings and the changes in family dynamics that may have occurred as a result of the COVID-19 pandemic. 31 , 33 , 34 The goals of this study were to explore the experience of living through the COVID-19 pandemic for youth with chronic pain, as well as siblings and parents of youth with chronic pain across Canada, and describe this experience using the theoretical foundation of the family adjustment and adaptation response model 35 to develop a substantive account.…”
Section: Introductionmentioning
confidence: 99%